2017
DOI: 10.1038/tp.2017.135
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerobic exercise on brain metabolism and grey matter volume in older adults: results of the randomised controlled SMART trial

Abstract: There is mounting evidence that aerobic exercise has a positive effect on cognitive functions in older adults. To date, little is known about the neurometabolic and molecular mechanisms underlying this positive effect. The present study used magnetic resonance spectroscopy and quantitative MRI to systematically explore the effects of physical activity on human brain metabolism and grey matter (GM) volume in healthy aging. This is a randomised controlled assessor-blinded two-armed trial (n=53) to explore exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 44 publications
2
67
0
5
Order By: Relevance
“…This hypothesis is substantiated by other findings involving aerobic exercise in older adults. A previous study using magnetic resonance spectroscopy in this cohort found no change in N‐acetylaspartate/choline levels in the exercise group, but decreased levels in the control group that were driven by increases in total choline levels (Matura et al, ), a finding that is commonly found in dementia patients. These findings pair with a previous cross‐sectional study which is found that brain tissue density losses found with normal aging were mitigated by aerobic fitness scores (Colcombe et al, ).…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…This hypothesis is substantiated by other findings involving aerobic exercise in older adults. A previous study using magnetic resonance spectroscopy in this cohort found no change in N‐acetylaspartate/choline levels in the exercise group, but decreased levels in the control group that were driven by increases in total choline levels (Matura et al, ), a finding that is commonly found in dementia patients. These findings pair with a previous cross‐sectional study which is found that brain tissue density losses found with normal aging were mitigated by aerobic fitness scores (Colcombe et al, ).…”
Section: Discussionmentioning
confidence: 53%
“…A previous voxel‐based morphometry (VBM) analysis of the data used in this study did not uncover any volumetric changes in GM (Matura et al, ). This may suggest that VBM has reduced sensitivity for detecting changes in brain microstructure compared to measures of MRI signal, such as R 1 .…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Exercise can slow the rate of cognitive decline among individuals suffering from AD; even general physical activity and higher fitness levels decrease risk of AD (Best, Chiu, Hsu, Nagumatsu, & Liu-Ambrose, 2015;Maass et. al, 2015;Matura et al, 2017;Nagumatsu et al, 2013;Voss et al, 2013). Nouchi et al (2014) studied the effects of shortterm exercise on cognitive functions among 64 healthy subjects over the age of 62.…”
Section: The Effect Of Exercise On the Progression Of Alzheimer's Dismentioning
confidence: 99%